Strategies for Teaching and Sustaining Mathematics as an Indispensable Tool for Technological Development in Nigeria - Daso, Peter Ojimba (Richtmann Publishing, 2012)
The world of today is predominantly shaped and controlled by the overwhelming influence of science andtechnology with the study of mathematics as a pivot. This is perhaps in recognition of the indispensablerole of mathematics in realizing the nation’s dream of rapid scientific and technological development. Thisalso portends the fact that the triangle of science, technology and mathematics should be vigorouslypursued by the Nigerian government. However, Nigeria’s effort to promote scientific and technologicalliteracy are not yet yielding the required dividends because basic strategies for teaching mathematics havebeen down-played by various government agencies. Despite the bare fact that Nigerian children still shyaway from the study of mathematics, issues in mathematics teaching strategies such the use of qualifiedteachers, teacher motivation by incentives and computer aided instructions should be adequatelyimplemented. This paper addressed the issues of strategies for teaching and sustaining mathematics as anindispensable tool for technological development in Nigeria. Some innovative teaching strategies weresuggested for demystifying mathematics in the Nigerian classroom. They include the strategy ofconstructivism, groupings into students’ ability and the use of instructional aids and games. The paperconcluded that if the various strategies of stimulating the interest of students in the teaching and learningof mathematics are put to use in any country, including Nigeria, a great deal of change may be seen.